O lixo é no lixo? Banhos de cinco minutos? E a culpa é do meu canudo de plástico? Por uma educação ambiental crítica na formação inicial de professores de Ciências Biológicas - Bressani, Eduardo Alves (Universidade Federal de São Carlos, 2023)
The present work starts from the hypothesis that each individual carries conceptions and Social Representations of Environment and Environmental Education as it is stated by Reigota (2010). Thus, we seek to analyze to what extent the conceptions of Environment and Environmental Education of Biology and Science Education undergraduate students from the daytime (CBL-So) and evening (CBLN-So) courses approach the Macro-Political-Pedagogical Trends classified by Layrargues and Lima (2014). The analysis was based on the responses collected through a semi-structured questionnaire disclosed through e-mails and WhatsApp groups. It used the qualitative research as a data collection method and the Discursive Textual Analysis stated by Moraes and Galiazzi (2006) as a data analysis method. Throughout the speeches gathered, it was possible to verify that the students simultaneously present pragmatic and critical views. Lastly, it is concluded that the prevalence of the pragmatic macrotrend is the result of a political project that aims to perpetuate the current economic system and, at the same time, the presence of critical perspectives points to the possibility of a new, critical and contextualized curriculums in pre-service teacher education.
Is the garbage in the garbage? Five-minute baths? And it's my straw's fault plastic? For a critical environmental education in the initial training of teachers of Biological Sciences
Keywords: Educação Ambiental Crítica; Meio Ambiente; Formação Inicial de Professores; Critical Environmental Education; Environment; Pre-service Teacher Education; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO